Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Smartphone Merek Samsung di Kota Banjarmasin - Riska Maulida Corneliani; Muhammad Hasanur Arifin; Rizki Muslim Hidayat; Nurul Wahyuni (Smart Business Journal (SBJ), 2026)
This study aims to analyze the influence of product quality and brand image on purchasing decisions of Samsung smartphone s in Banjarmasin City using a quantitative approach with an explanatory research type. The population in this study consists of people in Banjarmasin City who use Samsung smartphone s as their primary smartphone . The sample size in this study was 100 respondents. Data collection was carried out through the distribution of questionnaires to respondents who met the research criteria, and the data were analyzed using the SPSS program. The results of the study indicate that product quality has a significant effect on purchasing decisions. Brand image also has a significant effect on purchasing decisions. In addition, simultaneously product quality and brand image have a significant effect on purchasing decisions.